The Ethics of Ethics Reviews in Global Health Research: Case Studies Applying a New Paradigm - Breilh Paz y Miño, Jaime Eduardo (2013)
With increasing calls for global health research there is growing concern regarding the ethical challenges encountered by researchers from high-income countries (HICs) working in low or middle-income countries (LMICs). There is a dearth of literature on how to address these challenges in practice. In this article, we conduct a critical analysis of three case studies of research conducted in LMICs.We apply emerging ethical guidelines and principles specific to global health research and offer practical strategies that researchers ought to consider. We present case studies in which Canadian health professional students conducted a health promotion project in a community in Honduras; a research capacity-building program in South Africa, in which Canadian students also worked alongside LMIC partners; and a community-university partnered research capacity-building program in which Ecuadorean graduate students, some working alongside Canadian students, conducted community-based health research projects in Ecuadorean communities.We examine each case, identifying ethical issues that emerged and how new ethical paradigms being promoted could be concretely applied.We conclude that research ethics boards should focus not only on protecting individual integrity and human dignity in health studies but also on beneficence and non-maleficence at the community level, explicitly considering social justice issues and local capacity-building imperatives.We conclude that researchers from HICs interested in global health research must work with LMIC partners to implement collaborative processes for assuring ethical research that respects local knowledge, cultural factors, the social determination of health, community participation and partnership, and making social accountability a paramount concern.